Тhe Viscosity Study of Naftifine Hydrochloride Solution with a Combination of Polyethylene Glycols - S. I. Kosenkova; I. I. Krasnyuk; I. I. Krasnyuk (jr.) (Разработка и регистрация лекарственных средств)
Introduction. Naftifin hydrochloride is an antifungal drug from the allylamine group, which is used as a drug for external use in the treatment of onychomycosis. Quickly penetrates the skin and nails. It has antifungal, antibacterial and anti-inflammatory effects. It has a wide range of actions against many fungi that cause onychomycosis (dermatophytes, molds and yeast). In addition, it has an antibacterial effect in the ratio of gram-positive and gram-negative bacteria, reduces the risk of complicated course of the disease. It has a pronounced anti-inflammatory effect. Polyethylene glycols belong to the class of organic polymers of ethylene glycol. Polyethylene glycols are safe and widely used in pharmaceutical production, due to the variety of applications. The object of the study is a number of solutions of naftifin hydrochloride in different combinations and with different ratios of polyethylene glycols.Aim. The purpose of the work is to choose the optimal composition of the solution of naftifin hydrochloride. Achieve due to the viscosity of the prolonging action of the solution. Depending on the molecular weight of polyethylene glycol to determine the flow time of solutions. Choose among a number of samples with different ratios of polyethylene glycols, a solution with maximum viscosity.Materials and methods. To determine the viscosity of this solution, a capillary viscometry method was used on the vpzh-2 apparatus. «Exoderil» solution was chosen as a reference formulation.Results and discussion. Alternating different combinations of polyethylene glycol, we have increased the viscosity of the fluid naftifine hydrochloride, which has achieved a more accurate method of application of medicinal substances. During the study, it was determined that the solution «Exoderil» has a minimum viscosity, compared with all samples of the studied solutions.Сonclusion. The optimal viscosity of the solution of naftifin hydrochloride provides a prolonged action of the drug, due to a longer stay on the nail plate. Viscosity allows for more accurate application to the damaged nail, and reduces the loss of concentration of the active substance. Moisturizing properties of polyethylene glycols will help to reduce the severity of side effects (dryness, rarefaction), and provide a longer and more comfortable treatment of onychomycosis.